Training Translation Faculty at Universities in Kazakhstan - Maralbekkyzy, A. (MAQSUT NARIKBAYEV UNIVERSITY School of Liberal Arts. Astana, 2025)
The study explored the preparation of translation faculty at universities in Astana, Kazakhstan by examining how both MA Translation Studies students and graduates perceive their readiness and training to teach translation. This study was guided by the following research questions: how do students and graduates of MA Translation Studies programs perceive their readiness to work as translation faculty? What competencies do they develop in MA Translation Studies programs to qualify them for working as translation faculty? What educational practices within MA Translation Studies programs contribute to developing these competencies? Semi structured interviews were conducted with fourteen participants: eight second-year Master’s students currently enrolled in Translation Studies programs, and six graduates of MA Translation Studies programs who work as translation faculty at two universities in Astana, Kazakhstan, and have professional experience in translation and interpretation. Findings reveal that while participants felt confident in their translation/interpretation competencies, many lacked pedagogical preparedness. Their perceived readiness for faculty’s role was shaped by personal motivation, prior teaching experience, and the degree to which MA programs supported pedagogical development. Six key competencies emerged: translation and interpreting, pedagogical and didactic, interpersonal and communication, cognitive and research, ethical, and technological competencies. However, pedagogical competencies were often underdeveloped, revealing a gap between translation expertise and teaching preparedness. To address existing gaps in translation faculty preparation within MA Translation Studies programs, the study recommends integrating more pedagogy courses, expanding supervised teaching experiences, and promoting mentorship to bridge the theory-practice divide. Limitations include a small sample from two universities and reliance on self-reported data. Future research should involve iv broader samples, include perspectives of curriculum designers, and incorporate classroom observations to provide a more comprehensive understanding of faculty preparation in translation education.
Keywords: MA Translation Studies, translation faculty, readiness, translation and interpreting, pedagogical and didactic, interpersonal and communication, cognitive and research, ethical, and technological competencies